ALMASOP. A Rotating Feature Rich in Complex Organic Molecules in a Protostellar Core - Hsu, Shih-Ying; Lee, Chin-Fei; Johnstone, Doug; Liu, Sheng-Yuan; Liu, Tie; Bronfman, Leonardo; Chen, Huei-Ru Vivien; Dutta, Somnath; Eden, David J.; Hirano, Naomi; Juvela, Mika; Kim, Kee-Tae; et al. (The Astrophysical journal, 2025)
Interstellar complex organic molecules (COMs) in solar-like young stellar objects (YSOs), particularly within protostellar disks, are of significant interest owing to their potential connection to prebiotic chemistry in emerging planetary systems. We report the discovery of a rotating feature enriched in COMs, including CH 3 OH, CH 3 CHO, and NH 2 CHO, in the protostellar core G192.12-11.10. By constructing a YSO model, we find that the COM-rich feature is likely located within or near the boundary of the Keplerian disk. The image synthesis results suggest that additional heating mechanisms leading to a warm ring or a warm inner disk are required to reproduce the observed emission. We discuss possible origins of the COM-rich feature, particularly accretion shocks as a plausible cause for a warm ring. Additionally, molecules such as C 18 O, H 2 CO, DCS, H 2 S, and OCS exhibit distinct behavior compared to CH 3 OH, indicating a range of physical and chemical conditions within the region. The observed kinematics of H 2 S and OCS suggest that OCS resides in regions closer to the central protostar than H 2 S, consistent with previous experimental studies.